A newsreel history of the Third Reich. Volume 15 Allied aerial attacks [videorecording (DVD)]. (Artsmagic, 2008)
Shows the events of WWII from the viewpoint that was presented to the ordinary German people by the Nazi propaganda machine. This volume deals with the third part of 1943 and covers events from the Home front to meetings with German allies.